FAKTOR RISIKO KEJADIAN HEMOROID PADA SUPIR BIS AKAP DI POOL PO. GUMARANG JAYA - Yusmanedi Yusmanedi; Zulhafiz Mandala (Prodi Kedokteran Fakultas Kedokteran Universitas Malahayati, 2014)
Background: Hemorrhoids is a common disease, and has been there since antiquity, but a lot of people who don’tunderstand even don’t know about the symptoms and complications arising from the disease.Objective: The purpose of the research was to prove whether the food, the incidence of constipation, the type ofphysical activity, family history of hemorrhoids, bowel length is a factor - risk factors on the incidence of hemorrhoids in thedriver Inter-Province (AKAP).Methods: The research is a descriptive research that purpose to identify risk factors for the incidence ofhemorrhoids in the AKAP bus driver at POOL PO. Gumarang JAYA Bandar Lampung.Results: Over a period of 5 years (January 2009 - December 2014) PO Gumarang Jaya has a driver remains of 60people, and obtained a sample of 52 people who met the research criteria. And who have hemorrhoids 78.8%, while 21.2%did not have hemorrhoids, mostly in the age of 30-39 years on average education junior high school graduates, who haveconstipation as much as 73.1% so that the risk of constipation as much as 8,5 times from which isn’t constipation, of asmuch as 78.8% overall driver doesn’t perform physical activity so much risk just as much as 3,226 times, 53.8% ofrespondents come from families with no history of hemorrhoid and has great risk as much as 0,965 times, 71.2% ofrespondents in need time defecate more than 5 minutes so it has a great risk of0.479 times, 78.8% of respondents don’t eatfibrous foods so much risk as much as 0.479 times.